Olive & Pekoe : in four short walks - Davis, Jacky, 1966- (Greenwillow Books, an Imprint of HarperCollinsPublishers, 2019)
Playful puppy Pekoe and his good friend, Olive, an old dog with short legs, have different approaches as they enjoy a visit to the park, get caught in a thunderstorm, meet a chipmunk, and face a bully.